Baroreflex physiology studied in healthy subjects with very infrequent muscle sympathetic bursts - Diedrich, André (American Physiological Society, 2013)
Because it is likely that, in healthy human subjects, baroreflex mechanisms operate continuously, independent of experimental interventions, we asked the question, In what ways might study of unprovoked, very infrequent muscle sympathetic bursts inform baroreflex physiology? We closely examined arterial pressure and R-R interval responses of 11 supine healthy young subjects to arterial pressure ramps triggered by large isolated muscle sympathetic bursts. We triggered data collection sweeps on the beginnings of sympathetic bursts and plotted changes of arterial pressure (finger volume clamp or intra-arterial) and R-R intervals occurring before as well as after the sympathetic triggers. We estimated baroreflex gain from regression of R-R intervals on systolic pressures after sympathetic bursts and from the transfer function between cross-spectra of systolic pressure and R-R intervals at low frequencies. Isolated muscle sympathetic bursts were preceded by arterial pressure reductions. Baroreflex gain, calculated with linear regression of R-R intervals on systolic pressures after bursts, was virtually identical to baroreflex gain, calculated with the cross-spectral modulus [mean and (range): 24 (7–43) vs. 24 (8–45) ms/mmHg], and highly significant, according to linear regression (r(2) = 0.91, P = 0.001). Our results indicate that 1) since infrequent human muscle sympathetic bursts are almost deterministically preceded by arterial pressure reductions, their occurrence likely reflects simple baroreflex physiology, and 2) the noninvasive low-frequency modulus reliably reproduces gains derived from R-R interval responses to arterial pressure ramps triggered by infrequent muscle sympathetic bursts.